Adult linear IgA disease and chronic bullous disease of childhood: the association with human lymphocyte antigens Cw7, B8, DR3 and tumour necrosis factor influences disease expression. - Collier, P; Wojnarowska, F; Welsh, K; McGuire, W; Black, M (1999)
Linear IgA disease and chronic bullous disease of childhood are both subepidermal autoimmune blistering diseases. Class I and II major histocompatibility locus (MHC) antigen typing was performed on 60 patients (26 chronic bullous disease of childhood, 34 adult linear IgA disease), and the findings were correlated with the clinical course. The typing was performed using a lymphocyte microcytotoxicity assay, and the results were compared with a reference population of U.K. organ donors. Analysis of the tumour necrosis factor (TNF) locus was performed using sequence-specific oligonucleotides on a dot blot in 51 patients and compared with a random control population and human lymphocyte antigen (HLA) DR3 matched controls. The disease was found to be significantly associated with HLA Cw7 (chi2 = 19.24, P = 0.001), B8 (chi2 = 9.89, P = 0.04) and DR3 (chi2 = 10.47, P = 0.014), all components of the common Caucasian haplotype. There was also a close association between the disease and possession of HLA DR2 or 3 (chi2 = 16.34, P = 0.001). A reduction in the incidence of DR1 and DR4 (alleles carrying the rheumatoid motif) was observed, which is more marked in the children (chi2 = 8.34, P = 0.039). In the childhood group there was an increased frequency of B8, DR3 and DQ2 compared with the adults which included five of 26 who were homozygous for these antigens, a feature not seen in the adults, which may account for the differences seen between the two groups. Possession of HLA B8, DR3 and DQ2 probably facilitates earlier presentation of the disease as there is no evidence from our results that the adults and children differ fundamentally in their MHC associations. The rare TNF2 allele was found in 29 of 51 patients (expected 8.2, chi2 = 18. 3, P = 0.0001). This was more marked in the children (19 of 26). Patients with the TNF2 allele had a longer disease duration (5.3 years TNF2, 3.0 years TNF1).